Risk Factors for the Development of Critical Illness Polyneuropathy and Myopathy in a Pediatric Intensive Care Unit - Bilan, Nemat; Gaemi, Mir Reza; Shiva, Shadi (Iranian Journal of Child Neurology, 2011)
Objective Critical illness polyneuropathy and myopathy (CIPNM) is a major complication of severe critical illness. Previous studies have suggested that many risk factors such as sepsis, multiorgan failure, and neuromuscular blocking agents play a role in CIPNM pathogenesis. The aim of this study was to evaluate possible risk factors in the development of CIPNM in a pediatric intensive care unit (PICU). Materials & Methods In this observational study, we recruited 57 patients admitted in the PICU of the Tabriz Pediatric Hospital. CIPNM was diagnosed in 13 (22.8%) patients on the basis of the clinical and electrodiagnostic findings. Different variables such as age, sex, the pediatric risk of mortality (PRISM) score, duration of mechanical ventilation and PICU stay, accompanying pathologic conditions, medications, and in-hospital outcome were compared between the CIPNM and non-CIPNM groups. Results Compared to the non-CIPNM patients, the CIPNM patients showed significantly more frequent sepsis (6.8% vs. 38.5%, odds ratio [OR] = 8.5, 95% confidence interval [CI] = 1.7-43.1) and multiorgan dysfunction (43.2% vs. 76.9%, OR = 4.4, 95% CI = 1.1-18.2). Midazolam was administered more frequently in the non-CIPNM group than in the CIPNM group (88.6% vs. 53.8%, OR =0.2, 95% CI = 0.0-0.6). There was no significant difference between the 2 groups withrespect to parameters such as age, sex, PRISM score, duration of mechanical ventilation and PICU stay, other accompanying pathologic conditions, and other medications. The mortality rate was 4.5% in the non-CIPNM group and 15.4% in the CIPNM group.In the multivariable analysis, sepsis and midazolam administration were the only significant contributors to the development of CIPNM. Conclusion Sepsis is an independent risk factor for the development of CIPNM. However, midazolam administration seems to be an independent protective factor against CIPNM. Keywords: Critical illness polyneuropathy and Myopathy; pediatric intensive care unit; risk factors